Incidência do ITBI na integralização de capital social subscrito em holding patrimonial - Jankowski Junior, Romeu José (2024)
The purpose of this dissertation is to analyze the application of the tax benefit of the nontaxation of ITBI in transactions involving the payment of share capital by asset holding companies. This is a theoretical and bibliographical study, which involves descriptive research with a qualitative approach. It is structured as an introduction, development and conclusion. Initially, the approach to business structures will be contextualized in the pursuit of nontaxation, as a form of tax and succession planning. In development, aspects of the theory of the fundamental duty to pay taxes will be addressed, addressing issues related to contributory capacity and tax justice. Aspects inherent to tax planning, its context, application and opposability to the tax authorities will also be examined. Finally, the study will analyze the social function of property and, in particular, of the company, as an essential economic element in the context of the tax matrix and its fair application. The final intention is to identify whether, in the light of the studies carried out, asset holding companies can oppose the tax authorities' right to not levy ITBI on share capital payment transactions.